Ci, gender and social change among the Asmat of Papua, Indonesia - Daeli, Onesius Otenieli (Sidestone Press, 2020)
Ci' is the Asmat word for dugout canoe. The ci is an integral part of the everyday life of the Asmat - an ethnic group residing in eastern Indonesia in Papua province (formerly Irian Jaya) - who live in the middle of a huge tidal swampy area. Owning a ci is part of the Asmat's habitus because ci is a guarantee for mobility, both individually and collectively. The ci is essential for the everyday lives of the Asmat. However, the existence of these dugout canoes is now critical as they tend to be replaced by machinery boats.0This book uses a very simple piece of material culture, the ci, to introduce readers to the Asmat people and inform them how the Asmat people live. The ci becomes the focal point to understand gender power relations among the Asmat, particularly through social, economic, and spiritual dimensions. This volume is based on an anthropological fieldwork among the Asmat people for many years, and investigates the cultural significances of Asmat's ci by using 'symbolic and interpretive anthropology' as theoretical framework.